En quête de projet - Ambre Guichard (Éducation et Socialisation)
The requirement to formalize a "motivated educational project" on Parcoursup introduces an ordeal for justifying the coherence of study choices, which is now a stakeholder of selection-orientation at the entrance to university. Based on a case study taking interest in students who have reoriented themselves despite the appropriateness of their orientation choice, the article shows that the project does not necessarily meet the demand of coherence all along study paths, and that it sometimes even requires additional justification work. Analysis of the arguments used to justify the transition from one project to another highlights the way in which students have gradually acculturated to a temporalized conception of academic success. By getting to grips with the project as an instrument of reflexivity, students are finally coming to terms with the fact they have given up on their initial aspirations.